বাঙালির সমাজচিন্তা ও অন্যান্য প্রসঙ্গ - চৌধুরী, আনোয়ারউল্লাহ (ঢাকা : অনন্যা, 2014)
Articles chiefly on socio-political condition of Bangladesh.
গ্রন্থপঞ্জিগত নির্দেশিকা অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali.
Keywords: Bangladesh -- Politics and government -- 1971-; Bangladesh -- Social conditions